The effect of progressive hypoxia on swimming mode and oxygen consumption in the pile perch, Phanerodon vacca - Frank, LeeAnn C.; Prescott, Leteisha A.; Scott, Molly E.; Domenici, Paolo; Johansen, Jacob L.; Steffensen, John Fleng (Frontiers in Fish Science, 2024)
Hypoxia, an increasingly common stressor in coastal environments, lowers the scope for aerobic activity such as sustained swimming. This study examines the effect of self-depleting progressive hypoxia on swimming performance and oxygen consumption of the pile perch, Phanerodon vacca, at their optimal speed (Uopt =29 cm•s -1 ). P. vacca is a labriform, medianpaired fin (MPF) swimmer that exhibits a clear gait transition from primarily oxidative musclepowered, pectoral fin swimming to primarily anaerobic-powered, muscle burst swimming using the caudal fin (BCF) when facing high speeds or low oxygen. We expected that P. vacca swimming at Uopt would maintain oxygen consumption (ṀO2) alongside decreasing oxygen levels and continue to swim using MPF propulsion, until they approached their critical oxygen saturation at their optimal swimming speed (Scrit at Uopt). At this point we expected a gait transition to occur (i.e., from MPF to BCF propulsion), which is observed by a decrease in pectoral fin beat frequency and an increase in caudal fin or bursting frequency. Using a closedsystem swimming respirometer, P. vacca maintained strictly pectoral fin swimming at a consistent frequency and metabolic rate until reaching a critical oxygen saturation at their Scrit at Uopt of 38.6 ± 1.7% air saturation (O2sat). Below Scrit at Uopt, P. vacca significantly increased pectoral fin beat frequency, followed by a transition to caudal bursting at 33.7% O2sat. Switching to burst swimming allowed P. vacca to swim for 44.4 minutes beyond Scrit at Uopt until reaching 29.2% O2sat. Excess post hypoxia oxygen consumption (EPHOC) led to a significant increase in metabolic rate during recovery, which took 1.89 h to return to the routine metabolic rate (RMR). Time to return to RMR and excessive post hypoxia oxygen consumption did not differ when comparing exhaustive exercise and hypoxia exposure, suggesting that this species has an anaerobic energy reserve that does not differ when stressed during hypoxia or exercise. This study demonstrates that in hypoxia, the modulation of swimming mode from pectoral to caudal fin-based locomotion can maintain swimming well below Scrit at Uopt and provides a fundamental understanding of the physiological basis of sustained swimming in hypoxia.